Analisis Finansial Usahatani Cabai Keriting (Capsicum annum L) di Desa Lawalutolus, Kecamatan Tasifeto Barat, Kabupaten Belu. ( Studi Kasus pada Kelompok Wanita Tani Tunas Muda) - Serfandus Bria Bria; Adeline Norawati Hutapea; Umbu Joka (AGRIMOR, 2020)
The purpose aims to determine the financial feasibility of curly red papper farming in the Tunas Muda Farmers Women's Group with an area of ​​30 acres. Data analysis methods used include qualitative descriptive analysis to find out the general picture of curly red papper farming while to know the financial feasibility analysis using quantitative descriptive analysis including R/C Ratio, NPV, IRR, Break Event Point, and Payback Period. The results showed that the Tunas Muda Farmer Women Group in conducting curly chilli farming with an area of ​​30 acres had a farming cost of Rp 4.584.000; while the total revenue was Rp 14.014.000; The results of the financial feasibility analysis show that: 1). R/C Ratio value of 3,06; 2). NPV with a rate of 4.25% amounting to Rp 6,894,278. 3). IRR of Rp 36%. 4). BEP, the break even point for curly red papper farming at a production volume of 213 kg, at the reception and cost of Rp 4,584,000. 5). Payback Period as big as 3.64. So it can be said that the Financial Analysis of Curly red papper Farming in Lawalutolus Village, West Tasifeto District, Belu Regency is feasible to be carried out.